Bullying dan Pengaruhnya Terhadap Kecemasan Sosial pada Remaja di Aceh - Syiva Fitria; Thea Dwi Lestari (Prodi Bimbingan dan Konseling Islam, 2023)
Bullying or bullying is a phenomenon that continues to occur even though it is associated with various negative impacts. This study aims to examine the effect of bullying behaviour on social anxiety in the context of adolescent victims of bullying in Aceh. This research is a quantitative causality study. 30 teenagers (boys = 63%, girls = 37%) aged 13 to 18 who were victims of bullying voluntarily participated in this study. Data was collected using a questionnaire containing questions related to identity, bullying scale, and social anxiety scale. Data were analyzed using simple linear regression analysis. The results of the study show that there is an effect of bullying on social anxiety. The results showed that bullying significantly predicted social anxiety, b= .448, t(28) = 6.20, p<.001. Where bullying significantly affects social anxiety by 57.9% (R2=57.9, F(1,28)=38.55, p<.001). The results of this study can be used as a reference for policymakers and mental health practitioners in undertaking the phenomenon of bullying and its impact on social anxiety in adolescents.